(untitled) (Revista Argentina de Musicología, 2022)
The abundance of self-analysis that can be seen in a significant portion of Jorge Horst’s work tends to emphasize its ideological and political aspects in diverse ways. Furthermore, it connotes a world of productive receptions that has been scarcely explored. In this framework, the reception of Luigi Nono’s poetics undertakes a fundamental role and continues to be portrayed, among a considerable number of structural aspects, in the noticeable political dimension that both Horst’s works and self-analysis flaunt. Accordingly, we propose a journey centered in the all-interval row used by Nono since the mid-1950’s to delve into Horstian writings and compositions comprised between Serialismos (1990) and ALOF’ CO LAF’QUEN (2019) —for violin and marimba—, which allows us to emphasize the extension and permanence of the marked connection. At the same time, we account for a heterotopia that bonds Nonian materials and techniques with indeterminate procedures associated with the work of John Cage. In short, we attempt to demonstrate how the reception studied becomes a fundamental constituent of Horst’s poetics by involving both the applications of transtextual and cryptographic devices and the creation of theoretical notions, which ultimately involves providing elements to specify the functioning of the ideological-political in said poetics.